Factors associated with bacterial vaginosis in women with homosexual, bisexual and heterosexual practices - Mariana Alice de Oliveira Ignacio; Thayná Santos Buesso; Julia Andrade Pessoa Morales; Mariana de Castro Silva; Marcia Guimaraes da Silva; Marli Teresinha Cassamassimo Duarte (Brazilian Journal of Infectious Diseases, 2023)
Background: The factors associated with bacterial vaginosis in women with homosexual, bisexual and heterosexual practices are still poorly explored. Thus, the aim of this study was to analyze the factors associated with bacterial vaginosis in women with different sexual practices. Methods: Cross-sectional study that included 453 women, 149 Women with Homosexual practice (WSW); 80 bisexual Women (WSWM) and 224 Women with heterosexual practice (WSM). The diagnosis of bacterial vaginosis was performed by microscopic examination of the vaginal smears stained by Gram method and classified according to the Nugent et al. (1991) score. Data analysis was performed by Cox multiple regression. Results: Bacterial vaginosis was associated to years of education among WSW (0.91 [95% CI 0.82‒0.99]; p = 0.048) and non-white skin color (2.34 [95% CI 1.05‒5.19]; p = 0.037) between WSWM. Changing partners in the last 3-months (2.09 [95% CI 1.14‒3.82]; p = 0.017), inconsistent use of condoms (2.61 [95% CI 1.10‒6.20]; p = 0.030) and positive diagnosis of Chlamydia trachomatis (2.40 [95% CI 1.01‒5.73]; p = 0.048) were associated with bacterial vaginoses only in WSH. Conclusions: The factors associated to bacterial vaginosis differ between different sexual practices, suggesting that the type of sexual partner may influence the risk of developing this classic dysbiosis.